COVID-19 Prevention and Control Public Health Strategies in Shanghai, China. Issue 4 (July 2020) - Zhang, Ni; Shi, Tianqin; Zhong, Heng; Guo, Yijia
Abstract : Context: COVID-19 was characterized as a pandemic by the World Health Organization on March 11, 2020. This research aims to analyze the public health strategies to prevent and control COVID-19 in Shanghai, China, and provide recommendations for public health policy and interventions in the United States. Program: Based on the Social-Ecological Model, this research collected information for public health strategies from the Shanghai Municipal Health Commission and various Chinese websites. Evaluation: The daily confirmed new cases of COVID-19 decreased from 27 to 0 in 53 days since the first case of COVID-19 was confirmed in Shanghai on January 20, 2020. Discussion: The pattern of daily confirmed new cases suggests the effectiveness of public health strategies. This research also provides recommendations on the development and improvements of public health strategies in the U.S. by acknowledging the differences in political and social systems between the two countries. Abstract : Supplemental Digital Content is Available in the Text.